Preparation of a bispyridine based porous organic polymer as a new platform for Cu(ii) catalyst and its use in heterogeneous olefin epoxidation. (31st July 2018) - Yi, Jigyoung; Ahn, Hye Mi; Yoon, Jong Ho; Kim, Cheal; Lee, Suk Joong
Abstract : A new type of bispyridine (bpy) incorporated POP was prepared via a cobalt-catalyzed acetylene trimerization. Subsequent metalation of CuCl2 gave POP-Cu(ii ) which displayed outstanding olefin oxidation activity. Abstract : A new type of bispyridine (bpy) incorporated POP was prepared via a cobalt-catalyzed acetylene trimerization. Subsequent immobilization of CuCl2 gavePOP-Cu(ii ) . This new heterogeneous catalyst displayed outstanding olefin oxidation activity compared to its homogeneous analogue, suggesting that the degradation of the homogeneous catalyst was successfully inhibited by site isolation.